Mechanically induced integrin ligation mediates intracellular calcium signaling with single pulsating cavitation bubbles - Li, Fenfang (Theranostics, 2021)
Therapeutic ultrasound or shockwave has shown its great potential to stimulate neural and muscle tissue, where cavitation microbubble induced Ca(2+) signaling is believed to play an important role. However, the pertinent mechanisms are unknown, especially at the single-cell level. Particularly, it is still a major challenge to get a comprehensive understanding of the effect of potential mechanosensitive molecular players on the cellular responses, including mechanosensitive ion channels, purinergic signaling and integrin ligation by extracellular matrix. Methods: Here, laser-induced cavitation microbubble was used to stimulate individual HEK293T cells either genetically knocked out or expressing Piezo1 ion channels with different normalized bubble-cell distance. Ca(2+) signaling and potential membrane poration were evaluated with a real-time fluorescence imaging system. Integrin-binding microbeads were attached to the apical surface of the cells at mild cavitation conditions, where the effect of Piezo1, P2X receptors and integrin ligation on single cell intracellular Ca(2+) signaling was assessed. Results: Ca(2+) responses were rare at normalized cell-bubble distances that avoided membrane poration, even with overexpression of Piezo1, but could be increased in frequency to 42% of cells by attaching integrin-binding beads. We identified key molecular players in the bead-enhanced Ca(2+) response: increased integrin ligation by substrate ECM triggered ATP release and activation of P2X—but not Piezo1—ion channels. The resultant Ca(2+) influx caused dynamic changes in cell spread area. Conclusion: This approach to safely eliciting a Ca(2+) response with cavitation microbubbles and the uncovered mechanism by which increased integrin-ligation mediates ATP release and Ca(2+) signaling will inform new strategies to stimulate tissues with ultrasound and shockwaves.